1976
DOI: 10.1149/1.2132682
|View full text |Cite
|
Sign up to set email alerts
|

CdS ‐ Cu2 S  Solar Cells Fabricated on Cd2SnO4 ‐ Silica Substrates

Abstract: Cadmium stannate (Cd2SnO4) films of 112 per square sheet resistance and 85% average transmissivity (500-650 nm) have been grown by means of rf sputtering onto silica substrates. CdS-Cu2S thin film solar cells with conversion efficiencies greater than 5% for front and rear illumination have been fabricated. The reflection of transmitted light back through the cell has increased the light generated current. Fabrication techniques are described and current-voltage and spectral response measurements are presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This result is consistent with that reported by Smith et al, 32 who observed an increase in the Cd:Sn ratio with increases in the oxygen content of the sputtering atmosphere. Burton et al 33 also reported that the best results are obtained using pure oxygen plasma. This finding is consistent with the results of Wu et al 34 and Haacke, 14 who each noted improvement in the reproducibility of the film properties when the material was sputtered in pure oxygen.…”
Section: (1) Stoichiometry Controlmentioning
confidence: 96%
“…This result is consistent with that reported by Smith et al, 32 who observed an increase in the Cd:Sn ratio with increases in the oxygen content of the sputtering atmosphere. Burton et al 33 also reported that the best results are obtained using pure oxygen plasma. This finding is consistent with the results of Wu et al 34 and Haacke, 14 who each noted improvement in the reproducibility of the film properties when the material was sputtered in pure oxygen.…”
Section: (1) Stoichiometry Controlmentioning
confidence: 96%
“…The remarkably high corrosion resistance of Pb in most neutral and acidic conditions has resulted in its use as a construction and containment material for many corrosive chemicals and in corrosive environments (1,2). It has also led to the very successful combination of Pb and sulfuric acid in Pb/acid batteries (3).…”
Section: The Materials and Energy Research Centre Tehran Assisted In ...mentioning
confidence: 99%
“…In a previous paper (5), it was shown that the first step in Pb oxidation in these solutions involves the formation and dissolution of a Pb(OH)2 film, and the mechanism of these reactions was elucidated and described in detail. Using cyclic voltammetry (CV), as well as steady-state and transient potentiostatic methods, the following principal reactions ( [1], [2], and [3]) were found to occur in the potential range of about 150-300 mV vs. RHE Pb + OH-= (PbOH)ads + e- [1] (PbOH)ads + OH-= Pb(OH)z + e- [2] Pb(OH)~ + OH-= Pb(OH)3 [3] Under most experimental conditions, reaction [3] was *Electrochemical Society Active Member. **Electrochemical Society Student Member.…”
Section: The Materials and Energy Research Centre Tehran Assisted In ...mentioning
confidence: 99%
“…sputtering, electrical conductivities up to 6500 Ω −1 cm −1 have been achieved. 26,27 Instead, the conductivities observed in powder, 16 spray-deposited, 28 and "electroless" deposited 29 Cd 2 SnO 4 films do not show these high values. The observed differences in conductivity are essentially due to carrier mobility values that are approximately one order of magnitude lower than those measured in films obtained by R.F.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, many of the properties of both CdO and Cd 2 SnO 4 are originated by their nonstoichiometric composition, which, in turn, strongly depends on the synthetic procedure adopted. , In fact, in these compounds different amounts of n-type defects as cadmium interstitials or intrinsic oxygen vacancies produce donor states in the bulk bandgap, whose carrier concentration ranges from semiconductors to degenerate metallic conductors (CdO). ,, In Cd 2 SnO 4 films obtained by R.F. sputtering, electrical conductivities up to 6500 Ω –1 cm –1 have been achieved. , Instead, the conductivities observed in powder, spray-deposited, and “electroless” deposited Cd 2 SnO 4 films do not show these high values. The observed differences in conductivity are essentially due to carrier mobility values that are approximately one order of magnitude lower than those measured in films obtained by R.F.…”
Section: Introductionmentioning
confidence: 99%